IMPLEMENTASI METODE KETELADANAN RASULULLAH DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM TELAAH PEMIKIRAN ABDUL FATTAH ABU GHUDDAH - Abbas, Ngatmin; Rochmawan, Alfian Eko; Fathurrohman, Mukhlis; Ulfah, Yetty Faridatul (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This research delves into the implementation of the method of emulating Prophet Muhammad (peace be upon him) within the Islamic religious education curriculum using a literature-based approach. The book